DEVELOPMENT AND MODELING OF ENERGY-EFFICIENT PHOTOVOLTAIC SYSTEMS BASED ON GIS TECHNOLOGIES IN FERGANA CITY CONDITIONS (European Journal of Economics, Finance and Business Development, 2025)
This article presents the results of developing and modeling energy-efficient photovoltaic systems (PVS) for building rooftops in Fergana, Uzbekistan, using mathematical models and geographic information systems (GIS). The study encompasses an analysis of solar potential, operational loads, and system profitability. Simulations indicate that for a 300 m^2 rooftop with a 30° tilt angle, annual energy output reaches 98,400 kWh, with a payback period of 1.6–1.9 years under subsidies. The proposed methods achieve an accuracy of ±5–7% and are applicable for optimizing PVS placement in dense urban environments. Recommendations include using lightweight structures and ventilation to enhance efficiency.